The timing of adenomyosis diagnosis and its impact on pregnancy outcomes: a national population-based study - Jung, Young Mi; Wi, Wonyoung; Koo, Hwa Seon; Shim, Seung-Hyuk; Oh, Soo-Young; Lee, Seung Mi; Chung, Jin Hoon; Cho, SiHyun; Cho, Hyunjin; Oh, Min-Jeong; Cho, Geum Joon; Won, Hye-Sung (Obstetrics & gynecology science, 2024)
Adenomyosis impacts pregnancy outcomes, although there is a lack of consensus regarding the actual effects. It is likely, however, that the severity of adenomyosis or ultrasound findings or timing of diagnosis can have different effects on adverse pregnancy outcomes (APOs). In this study, we aimed to investigate the impact of the timing of adenomyosis diagnosis on pregnancy outcomes. Singleton pregnant women who delivered between 2017 and 2022 were analyzed based on the timing of adenomyosis diagnosis, using a national database. The final cohort was classified into three groups: 1) group 1, without adenomyosis; 2) group 2, those diagnosed with adenomyosis before pregnancy; and 3) group 3, those diagnosed with adenomyosis during pregnancy. A total of 1,226,475 cases were ultimately included in this study. Women with a diagnosis of adenomyosis had a significantly higher risk of APOs including hypertensive disorder during pregnancy (HDP), gestational diabetes mellitus (GDM), postpartum hemorrhage, placental abruption, preterm birth, and delivery of a small-for-gestational-age infant even after adjusting for covariates. In particular, concerning HDP, the risk was highest in group 3 (group 2: adjusted odds ratio [aOR], 1.15 vs. group 3: aOR, 1.36). However, the highest GDM risk was in group 2 (GDM; group 2: aOR, 1.24 vs. group 3: aOR, 1.04). The increased risk of APO differed depending on the timing of adenomyosis diagnosis. Therefore, efforts for more careful monitoring and prevention of APOs may be necessary when such women become pregnant.